Biliopancreatic diversion with duodenal switch improve polycystic ovary syndrome with decreased serum ceramides - Li, Xiaochuan; Chen, Haomin; Li, Pengyu; Wang, Mingfei; Wu, Dalin; Liu, Juan; Chen, Weijie (Frontiers in Endocrinology, 2026)
BackgroundPolycystic ovary syndrome (PCOS) is characterized primarily by insulin resistance and reproductive disorders. Biliopancreatic diversion with duodenal switch (BPD/DS) could significantly improve insulin sensitivity with significantly elevated level of bile acids. We aimed to explore changes in PCOS manifestations after BPD/DS and the possible mechanisms.MethodsTwenty PCOS rat models were assigned into the BPD/DS group and the sham BD (S-BPD) group randomly. The fasting blood glucose, bile acids, and ceramides levels in serum samples were assessed.ResultsThe reproductive disorders of BPD/DS group were almost completely restored 8 weeks after surgery, and the AUCOGTT value and the AUCITT value were statistically less than those of the S-BPD group (P =0.001). The concentration of serum testosterone, luteinizing hormone, and follicle-stimulating hormone of the BPD/DS group was statistically less than that of the S-BPD group (P <0.05). Moreover, high level of bile acids and low level of ceramides were observed in the BPD/DS group (P <0.001). Bile acid sequestrant was given to the BPD/DS group rats for 1 week, the level of bile acids decreased and ceramides increased, the insulin resistance worsened. The AUCOGTT value increased from 818.3 ± 297.3 mmol/L·min to 1147.9 ± 167.9 mmol/L·min (P =0.007) and the AUCITT value increased from 525.6 ± 52.3 mmol/L·min to 577.7 ± 102.9 mmol/L·min (P =0.023).ConclusionsOur study showed the improvement of insulin resistance in PCOS models after BPD/DS with decreased serum ceramides. The sequestrant of bile acid reversed the improvement of insulin resistance with higher ceramides level.